Penerapan Restorative Justice Di Unit 2 Satreskrim Pidsus Polres Blitar Berdasarkan Peraturan Kapolri Nomor 8 Tahun 2021 - Ainaya Nurhayati; Novita Setyoningrum (Jurnal Relasi Publik, 2023)
The purpose of this study is to find out the settlement of this crime of theft by using the concept of Restorative Justice, as well as what are the considerations of the Police and Complainants in implementing this Restorative Justice against the perpetrators of the Teak Wood Theft Crime. The method used in this research is empirical juridical research which is the implementation of normative legal provisions in the form of (laws) as well as based on legal reality in society (empirical). The data used in this study are primary data and secondary data, primary data is data obtained from respondents through interviews, and secondary data is data obtained from books, journals, legislation, websites. The results of this study can be concluded that the crime of theft is an ordinary offense that can be resolved through discretionary Restorative Justice or decision-making carried out by the Police based on KAPOLRI regulation Number 8 of 2021 concerning Handling of Crimes Based on Restorative Justice. By revoking the report from the complainant or peacefully from both parties, the Investigator then re-examines both the victim and the witness with a statement revoking the Minutes of Examination. The revocation resulted in the non-fulfillment of the elements of evidence, so that the Investigator could stop his investigation with the consideration of the victim and the Investigator. According to the data the author obtained from the Special Criminal Investigation Unit of the Blitar District Police, from 2021 to 2023 as of June there were 24 Illegal Logging cases at the Blitar District Police, and only 3 cases were resolved through Restorative Justice, with a percentage calculation of 12.5% ​​only . Even though Restorative Justice can be carried out, it must still meet the material and formal requirements based on the Chief of Police Regulation Number 8 of 2021, especially when it comes to the environment.